(untitled) (Materiali di Estetica. Terza serie, 2019)
The author illustrates the first years of Gillo Dorfles’ life, starting from his childhood in Genoa during the First World War, the years of high schools in Trieste, his studies at the Faculty of Medicine in Milan and Rome. Subsequently, the author analyses Dorfles’ writings on Aesthetics, the poems and the pictorial works produced by Dorfles from the 1930s till 1948 (the year of the creation of the Movement for Concrete Art) and until 1951 (the year of the foundation of the magazine “Aut aut”).